Mainstreaming green job issues into national employment policies and implementation plans: a review - van de Ree, Kees (Geneva, 2017)
"Effectively mainstreaming environmental sustainability in national employment policies calls for increased policy coherence between employment and environmental goals, and policy-oriented research to assess the impact of environmentally friendly technologies and patterns of production and consumption on employment in order to inform and facilitate social dialogue throughout the policy-making process. It also requires solid coordination mechanisms to enable environment and employment actors to work together. This paper documents in detail the type of measures that an increasing number of countries are adopting to promote more and better employment and a just transition to environmental sustainability."